Analysis Of Creativity And Communication On The Work Performance Of ASN Employees At The Regional Finance And Asset Agency Of North Sumatra Province - Deswita Fitri; Muhammad Toyib Daulay; Kiki Farida Ferine (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The performance of the State Civil Service plays a crucial role in improving the quality of governance, particularly in regional financial management agencies, which play a strategic role in budget planning, implementation, and reporting. The North Sumatra Provincial Finance and Asset Agency is required to adapt to regulatory dynamics, developments in information technology, and the complexities of regional financial management. Therefore, this study aims to analyze the impact of creativity and communication on the work performance of civil servants at the Regional Civil Service Agency of North Sumatra Province. The research approach chosen in this study is a quantitative associative method. The results of the study indicate that creativity has a positive and significant effect on employee work performance, with a calculated t value of 8.297 and a regression coefficient of 0.530. Similarly, communication has a positive and significant effect, indicated by a calculated t value of 6.235 and a regression coefficient of 0.264. Simultaneously, creativity and communication have a significant effect on work performance, evidenced by a calculated F value of 41.305 with a significance of 0.000 and a coefficient of determination (R²) of 0.484, which means that both variables are able to explain 48.4% of the variation in ASN employee work performance. Thus, this study concludes that creativity and communication are two important factors that need to be strengthened to improve ASN employee work performance.